(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud computing multi-tenancy feature, which provides privacy, security and access control challenges, because of sharing of physical resources among untrusted tenants. In order to achieve safe storage, policy based file access control, policy based file assured deletion and policy based renewal of a file stored in a cloud environment, a suitable encryption technique with key management should be applied before outsourcing the data. This paper implements secure cloud storage by providing access to the files with the policy based file access using Attribute Based Encryption (ABE) scheme with RSA key public-private key combination. Private Key is the combination of the user’s credentials. So that high security will be achieved. Time based file Revocation scheme is used for file assured deletion. When the time limit of the file expired, the file will be automatically revoked and cannot be accessible to anyone in future. Manual Revocation also supported. Policy based file renewal is proposed. The Renewal can be done by providing the new key to the existing file.